The importance of reproductive isolation in driving diversification and speciation within Peruvian mimetic poison frogs (Dendrobatidae) - Ugo Lorioux-Chevalier; Mathieu Chouteau; Alexandre-Benoit Roland (Scientific Reports, 2024)
Abstract To explain how populations with distinct warning signals coexist in close parapatry, we experimentally assessed intrinsic mechanisms acting as reproductive barriers within three poison-frog species from the Peruvian Amazon belonging to a Müllerian mimetic ring (Ranitomeya variabilis, Ranitomeya imitator and Ranitomeya fantastica). We tested the role of prezygotic and postzygotic isolation barriers between phenotypically different ecotypes of each species, using no-choice mating experiments and offspring survival analysis. Our results show that prezygotic mating preference did not occur except for one specific ecotype of R. imitator, and that all three species were able to produce viable inter-population F1 hybrids. However, while R. variabilis and R. imitator hybrids were able to produce viable F2 generations, we found that for R. fantastica, every F1 hybrid males were sterile while females remained fertile. This unexpected result, echoing with Haldane’s rule of speciation, validated phylogenetic studies which tentatively diagnose these populations of R. fantastica as two different species. Our work suggests that postzygotic genetic barriers likely participate in the extraordinary phenotypic diversity observed within Müllerian mimetic Ranitomeya populations, by maintaining species boundaries.